SUN-254 A Long-Term, Phase IV Study of Omnitrope®, a Recombinant Human Growth Hormone (rhGH), in Short Children Born Small for Gestational Age (SGA) - Schwarz, Hans-Peter (J Endocr Soc, 2019)
Background: Children born SGA are predisposed to metabolic abnormalities. While the therapeutic benefit of rhGH therapy in improving height is widely recognised, it can affect carbohydrate metabolism, potentially inducing diabetes. This ongoing, prospective study aims to evaluate the long-term safety and efficacy of Omnitrope® (somatropin) in children born SGA. Here we present data from an interim analysis conducted in April 2017. Methods: Prepubertal children born SGA were recruited according to standard criteria; those included are treated with Omnitrope® and followed at predetermined time intervals until final height is reached. Results: Overall, 278 children were enrolled in the study, and 13 have discontinued the study due to non-response to treatment (height velocity standard deviation score [HVSDS] < +1 after 1 year). Mean (SD) age at baseline and latest visit was 7.86 (2.74) and 13.08 (3.36) years, respectively. To date, there have been no confirmed cases of new-onset diabetes mellitus. Mean oral glucose tolerance (2h), HbA1c, and fasting glucose levels have remained relatively stable from baseline to latest visit; however, mean (SD) fasting insulin levels increased from 35.65 (34.69) pmol/L at baseline to 53.68 (35.93) pmol/L after 1 year and to 70.46 (45.60) pmol/L at latest visit. Auxological measurements indicate improvements in height parameters from baseline to latest visit, including mean height SDS (net gain Δ+1.65) and peak-centred HVSDS (baseline: -2.11; Year 1: +4.16; Year 2: +2.23; latest visit, +0.19). Similarly, mean (SD) IGF-I SDS increased from -1.08 (1.02) at baseline to 0.64 (1.21) after 1 year and to 0.53 (1.27) at latest visit. A total of 2075 adverse events (AEs) have been reported in 242 patients; 99% of these AEs were of mild-to-moderate intensity. Serious AEs (n=125) have been reported in 68 patients; 4 of these (in 3 patients) were suspected as possibly related to study treatment, and only one resulted in study drug being permanently discontinued. Conclusions: In this long-term study of Omnitrope® in children born SGA, no patient has developed new-onset diabetes during rhGH treatment and there have been no concerning or clinically relevant safety findings. In addition, Omnitrope® treatment has been effective, as documented by all height parameters. Patients receiving rhGH treatment should be closely monitored for detrimental changes in carbohydrate metabolism.